Two-Injection Start Regimen of Long-Acting Aripiprazole in 133 Patients With Schizophrenia. Issue 1 (January 2023) - Cuomo, Alessandro; Aguglia, Eugenio; Biagini, Stefano; Carano, Alessandro; Clerici, Massimo; D'Agostino, Armando; De Filippis, Sergio; De Giorgi, Serafino; Goracci, Arianna; Libri, Claudia; Lombardi, Francesco; Lupi, Matteo; et al.
Abstract: Purpose/Background: Based on a population-pharmacokinetic model, the European Medicines Agency has recently approved a simplified starting strategy of aripiprazole once a month (AOM), injectable and long-acting antipsychotic, with two 400 mg injections and a single oral 20 mg dose of aripiprazole, administered on the same day, instead of 1 injection and 14 daily administrations of concurrent oral aripiprazole. However, to our knowledge, no previous study has reported the safety and tolerability of this regimen in real-world patients. Methods/Procedures: We retrospectively reviewed medical records of 133 patients who received the newly approved 2-injection start regimen as part of their standard care in 10 Italian clinical centers. Findings/Results: Adverse effects were mild or moderate, with no clinically evident difference from the adverse effects observed in previous trials where AOM was started with a single injection followed by 14 days of orally administered aripiprazole. None of the patients who started AOM after the 2-injection start regimen experienced severe adverse effects or severe adverse effects. Implications/Conclusions: The coadministration of 2 injections of 400 mg aripiprazole and 20 mg oral aripiprazole was not associated with safety concerns beyond those reported after a single injection followed by 14 days of orally administered aripiprazole. Our results should be interpreted with caution, due to the limited sample size and to the retrospective design of the study.